Giardia duodenalis induces pathogenic dysbiosis of human intestinal microbiota biofilms. Issue 6 (May 2017) - Beatty, Jennifer K.; Akierman, Sarah V.; Motta, Jean-Paul; Muise, Stacy; Workentine, Matthew L.; Harrison, Joe J.; Bhargava, Amol; Beck, Paul L.; Rioux, Kevin P.; McKnight, Gordon Webb; Wallace, John L.; Buret, Andre G.
Graphical abstract: Highlights: We examined mechanisms whereby Giardia duodenalis interacts within the multi-species gastrointestinal tract (GI) microbiota. The impact of Giardia on the structure of bacterial biofilms grown directly from intestinal mucosal biopsies was elucidated. Our data contribute to greater understanding of the impact of an altered microbiome in chronic GI disease development. Abstract: Giardia duodenalis is a prevalent cause of acute diarrheal disease worldwide. However, recent outbreaks in Italy and Norway have revealed a link between giardiasis and the subsequent development of chronic post-infectious irritable bowel syndrome. While the mechanisms underlying the causation of post-infectious irritable bowel syndrome remain obscure, recent findings suggest that alterations in gut microbiota communities are linked to the pathophysiology of irritable bowel syndrome. In the present study, we use a laboratory biofilm system to culture and enrich mucosal microbiota from human intestinal biopsies. Subsequently, we show that co-culture with Giardia induces disturbances in biofilm species composition and biofilm structure resulting in microbiota communities that are intrinsically dysbiotic – even after the clearance of Giardia . These microbiota abnormalities were mediated in part by secretory-excretory Giardia cysteine proteases. Using in vitro cell culture and germ-free murine infection models, we show that Giardia -induced disruptions of microbiota promote bacterial invasion, resulting in epithelial apoptosis, tight junctional disruption, and bacterial translocation across an intestinal epithelial barrier. Additionally, these dysbiotic microbiota communities resulted in increased activation of the Toll-like receptor 4 signalling pathway, and overproduction of the pro-inflammatory cytokine IL-1beta in humanized germ-free mice. Previous studies that have sought explanations and risk factors for the development of post-infectious irritable bowel syndrome have focused on features of enteropathogens and attributes of the infected host. We propose that polymicrobial interactions involving Giardia and gut microbiota may cause persistent dysbiosis, offering a new interpretation of the reasons why those afflicted with giardiasis are predisposed to gastrointestinal disorders post-infection.